The Use of Peer Tutor Approach to Improve Student Learning Outcomes and Motivation in Islamic Learning at SD Negeri Lapahan Buaya - Kusmawati; Afni, Nur (Journal of Indonesian Primary School, 2025)
This study aims to explore the effectiveness of the peer tutoring approach in improving student learning outcomes and motivation in Islamic Education learning at SD Negeri Lapahan Buaya. This study used a quasi-experimental design, involving an experimental group that participated in peer tutoring sessions and a control group that participated in traditional lecture-based teaching methods. Data were collected through pre-test and post-test, student motivation survey, classroom observation, and student feedback. The results showed a significant increase in learning outcomes, where students in the experimental group showed better ability in remembering and applying Islamic teachings compared to the control group. In addition, the peer tutoring approach also had a positive effect on student motivation, as seen from increased participation, enthusiasm, and self-confidence in learning. Students expressed a preference for peer tutoring sessions, citing clearer explanations and more engaging learning experiences. These findings suggest that peer tutoring is an effective method in improving student learning outcomes and engagement in Islamic Education. Based on these findings, it is recommended that the peer tutoring approach be integrated into the Islamic Education curriculum to create a collaborative and student-centered learning environment.